Implementasi Model Extreme Programming dalam Pengembangan Sistem Simulasi Tes TOEFL - Rahman, Reyvi; Khaira, Ulfa; Abidin, Zainil (TIN: Terapan Informatika Nusantara, 2025)
English proficiency is a key requirement in both academic and professional settings, with TOEFL serving as a standardized measure of competency. However, many candidates are unprepared for this exam due to a lack of understanding and practice that simulates actual test conditions. Yanto Tanjung English Academy, a course provider offering online TOEFL instruction, currently lacks a comprehensive test simulation facility. Therefore, this research aims to develop a web-based TOEFL test simulation system to provide a realistic exam experience, enabling participants to be better prepared and more confident. The system was developed using the Extreme Programming (XP) method, which consists of planning, design, coding, and testing phases. Testing was conducted using a Test-Driven Development (TDD) approach to ensure the system's functionality and alignment with user requirements. The results show that all main features are accessible, as evidenced by an efficient average execution time of 2.126 seconds across all tested features. This performance data confirms that the TDD approach successfully yielded a system that is not only functional but also responsive for its users. Furthermore, the system received a high acceptance rate from both stakeholders and course participants. This system is expected to enhance the effectiveness of independent and flexible TOEFL learning and to serve as a beneficial digital solution for course participants and the general public wishing to practice TOEFL online